2017
DOI: 10.7860/jcdr/2017/21532.9851
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal Schwannoma – A Case Report

Abstract: A 35-year-old man presented with a history of nasal blockage more on the right side since two years. Other symptoms included rhinorrhoea, headache, recurrent epistaxis, mouth breathing and disturbed sleep since six months.Local examination revealed right and left nostril showing pale polypoid mass, insensitive to touch and it did not bleed on touching. Probe could be passed all around it. CT revealed mildly enhancing soft tissue density lesion arising from right maxillary sinus and extending into right nasal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Wong E et al [8] reported a case of sinonasal schwannoma in sixth decade in their case report. Mitra B et al [2] , Vaidya MM et al [3] , Dhawle MS et al [4] and Mangubat EZ et al [6] documented schwannoma in male patient. On the contrary, Singh M et al [5] , Mosalleum EMA [7] and Wong E et al [8] reported the lesion in female patients in their case reports.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Wong E et al [8] reported a case of sinonasal schwannoma in sixth decade in their case report. Mitra B et al [2] , Vaidya MM et al [3] , Dhawle MS et al [4] and Mangubat EZ et al [6] documented schwannoma in male patient. On the contrary, Singh M et al [5] , Mosalleum EMA [7] and Wong E et al [8] reported the lesion in female patients in their case reports.…”
Section: Discussionmentioning
confidence: 99%
“…[7] In contrast to other lesion, Schwannoma shows characteristic histopathological features. [4] Neurofibromas are positive for S-100, EMA and NF. Immunoreactivity for EMA in meningioma can be helpful to exclude the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations